Study of the Factors that Influence the Completion of the Thesis of Master of Health Professions Education Graduates: A Qualitative Study - Salma Ambreen Shahab, Iram Tassaduq, Ayesha Haque, Aqsa Naheed, Maleeha Zafar, Iram Zakria (Journal of Rawalpindi Medical College, 2021)
Objective: To investigate the experience of timely thesis completion by the graduates of the Master of Health Professions Education (MHPE) program in Pakistan. Study Design: Qualitative interpretative study design. Settings: Riphah University Islamabad and HITEC-IMS Taxila. Duration: May 2018 to June 2019. Materials and Methods: Data was collected by semi-structured interviews. All interviews were carried out in person. Detailed notes were taken, and conversations were audio-recorded. Three authors analyzed data independently using iterative thematic analysis. Inconsistencies were resolved through discussion. Results: Two major themes out of five were identified: Intrinsic attributes of the graduates and the role of the supervisor. including sub-themes of intrinsic motivation, self-regulation, age of the participant, supervisor-trainee relationship, supervisor’s availability, supervisor’s commitment, personality traits of the supervisor. Periods of face-to-face contact sessions were considered to increase internal motivation during which participants believe to have greater self-regulation. Positive relationship with a committed supervisor who was readily available and had a friendly, yet professional attitude aided in the completion of the thesis on time while a supervisor lacking these traits posed challenges for the graduates. Conclusion: Several factors were identified which influenced thesis completion among the graduates of MHPE in Pakistan. The five major ones consisted of the following, 1) Research Project-Related Problems; 2) Support System; 3) Supervisor Guidance; 4) Attributes of the Researcher; 5) Conducive Research Environment. These results can help influence policies to evaluate and improve this program.